Near‐Infrared Tandem Organic Photodiodes for Future Application in Artificial Retinal Implants. Issue 51 (15th October 2018) - Simone, Giulio; Di Carlo Rasi, Dario; de Vries, Xander; Heintges, Gaël H. L.; Meskers, Stefan C. J.; Janssen, René A. J.; Gelinck, Gerwin H.
Abstract: Photovoltaic retinal prostheses show great potential to restore sight in patients suffering from degenerative eye diseases by electrical stimulation of the surviving neurons in the retinal network. Herein, organic photodiodes (OPDs) sensitive to near‐infrared (NIR) light are evaluated as photovoltaic pixels for future application in retinal prostheses. Single‐junction and tandem OPDs are compared. In the latter, two nominally identical single‐junction cells are processed on top of each other, effectively doubling the open‐circuit voltage ( V OC ). Both single‐junction and tandem OPD micropixels can deliver the required charge to stimulate neurons under pulsed NIR light at physiologically safe intensities when connected to stimulating microelectrodes in a physiological saline solution. However, only tandem OPD pixels can cover the entire charge per pulse neural stimulation window due to their higher V OC (≈1.4 V). This demonstrates the viability of high‐resolution retinal prostheses based on flexible OPD arrays. Abstract : Organic photodiodes (OPDs) sensitive to near‐infrared light are evaluated for their application in artificial retinal implants. The electrical charge photogenerated by tandem OPD micropixels reaches the typical neural stimulation levels upon 4 ms light pulses at physiologically safe intensities. This paves the way toward the future development of high‐resolution retinal prostheses based on flexible OPD arrays.